Bilateral chemogenetic activation of intratelencephalic neurons in motor cortex reduces spontaneous locomotor activity in mice - Mihai Atudorei; Christian del Agua Villa; Ulrik Gether; Maria Angela Cenci; Hartwig Roman Siebner; Mattias Rickhag (Neurobiology of Disease)
Intratelencephalic neurons are a crucial class of cortical principal neurons that heavily innervate the striatum and cortical areas bilaterally. Their extensive cortico-cortical and cortico-striatal connectivity enables sensorimotor integration within the telencephalon, but their role in motor control remains poorly understood. Here, we used a chemogenetic approach to explore the role of intratelencephalic neurons in spontaneous locomotor activity. Bilateral chemogenetic activation of intratelencephalic Tlx3+ neurons in the mouse motor cortex reduced spontaneous locomotor activity in the open field, increasing states of freezing and immobility. This anti-motor effect was achieved in separate experiments with either administration of two chemogenetic actuators, clozapine N-oxide and deschloroclozapine. A systemic administration of the dopamine D1 receptor agonist SKF82958 reversed the chemogenetic effect on locomotor activity. Selective chemogenetic stimulation of intratelencephalic neurons was confirmed through post-mortem c-Fos quantification in cortical layer 5 Tlx3+ neurons. The results establish a causal link between the activity level of intratelencephalic neurons in the motor cortex, spontaneous locomotor activity in the open field, and the dopamine system. The findings are compatible with the hypothesis that intratelencephalic neurons regulate spontaneous motor behavior via its bilateral cortico-striatal projections.